Running and metabolic demands of elite Rugby Union assessed using traditional, metabolic power, and heart rate monitoring methods - Dubois, R.; Paillard, T.; Lyons, M.; McGrath, D.; Maurelli, O.; Prioux, J. (Journal of Sports Science & Medicine, 2017)
The aims of this study were (1) to analyze elite rugby union game demands using 3 different approaches: traditional, metabolic and heart rate-based methods (2) to explore the relationship between these methods and (3) to explore positional differences between the backs and forwards players. Time motion analysis and game demands of fourteen professional players (24.1 ± 3.4 y), over 5 European challenge cup games, were analyzed. Thresholds of 14.4 km·h-1, 20 W.kg-1 and 85% of maximal heart rate (HRmax) were set for high-intensity efforts across the three methods. The mean % of HRmax was 80.6 ± 4.3 % while 42.2 ± 16.5% of game time was spent above 85% of HRmax with no significant differences between the forwards and the backs. Our findings also show that the backs cover greater distances at high-speed than forwards (% difference: +35.2 ± 6.6%; p<0.01) while the forwards cover more distance than the backs (+26.8 ± 5.7%; p<0.05) in moderate-speed zone (10-14.4 km·h-1). However, no significant difference in high-metabolic power distance was found between the backs and forwards. Indeed, the high-metabolic power distances were greater than high-speed running distances of 24.8 ± 17.1% for the backs, and 53.4 ± 16.0% for the forwards with a significant difference (+29.6 ± 6.0% for the forwards; p<0.001) between the two groups. Nevertheless, nearly perfect correlations were found between the total distance assessed using the traditional approach and the metabolic power approach (r = 0.98). Furthermore, there is a strong association (r = 0.93) between the high-speed running distance (assessed using the traditional approach) and the high-metabolic power distance. The HR monitoring methods demonstrate clearly the high physiological demands of professional rugby games. The traditional and the metabolic-power approaches shows a close correlation concerning their relative values, nevertheless the difference in absolute values especially for the high-intensity thresholds demonstrates that the metabolic power approach may represent an interesting alternative to the traditional approaches used in evaluating the high-intensity running efforts required in rugby union games.